To Mecca on Pilgrimage on Foot and Camel-back: The Jordanian Darb al-Hajj. (November 2015) - Dauphin, Claudine; Ben Jeddou, Mohamed; Castex, Jean-Marie
Abstract : Literary, archaeological and cartographic data were collated to reconstruct the Darb al-Hajj al-Shami, stretching from Damascus to Mecca and bisecting Jordan longitudinally (7th-15th centuries). This was succeeded by the Ottoman route (16th-early 20th centuries), probably planned by Sinan, the famous architect of Sultan Suleiman the Magnificent, and ultimately by the Hijaz Railway. Examination of the relationship between these three routes and landscape elements (altitude, slope, relief, orientation, distance to hydrographic network, springs), while taking into account visibility, security, climate, and obstacles of the terrain, enabled us to define environmental parameters, which were integrated into GIS analyses. These proved how the Umayyad to Mamluk route adapted to the changing terrain, whilst the Ottoman route was an artificial creation that moulded the environment according to a global project of civil engineering.